Culture-creative potential of sacral experience: theoretical and methodological analysis - V. Y. Golovei, (Ukrainian Cultural Studies, 2017)
The purpose of the article is to analyze the cultural potential of sacred experience and highlight the main methodological approaches to its study. The sacred experience is explicated as an experience of correlation with the absolute dimension of being, its experience and comprehension. The concept of "Sacred experience" defines a culturally organized space that acquires a specific form for each culture and is structured as a meaningful hierarchical world full of spiritual and symbolic meanings. The experience of the sacred is based on direct experience of eternity and the totality of existence as a living reality. This experience is "the experience of being" the primary expression of existential guidance, global anthropological orientation. It integrates the dominant spiritual orientation in the human world and understanding of the system itself. Sacred experience based implicitly in present most important human endeavour, promotes the formation of the humanity. This experience permeates the entire story as vertical as the Earth's axis, culminating in the transcendent dimension - where a person entrusts himself to Absolute (God, being, good, eternal, etc.). We can say that any strategy or implemented anthropological model has its core generating a sacred experience. The author asserts that the experience of Holy is distinguished by ontological content and nature. It is an experience of symbolic acts of transcendence that create ontological horizon of being. At the same time, this is an experience of cultural creation and self-creation, which forms the sense foundations of human existence, reveals and confirms the human nature. Loss of sacred power and constitutive force of the sacred dimension interpreted as a manifestation of a kind of "weakening being", de-ontologization of culture, that accompanied the release of simulative and destructive potential and leads to a decrease in the intensity and quality of cultural development.
Keywords: Sacral experience, culture, sacred, profane, religious, secular